Magnetic nanocluster formation of Fe ions embedded in SiO2 and Al2O3 substrates - Bharuth-Ram, K.; Ronning, Carsten; Doyle, T. B. (MRS Advances, 2018)
Research focus in recent years on magnetic behaviour of transition metal (TM) ions embedded in semiconductors has shifted from intrinsic effects to extrinsic effects such as the formation of nanoclusters of the TM ions and the influence of the host matrix on their magnetic behaviour. Our studies, using conversion electron Mössbauer Spectroscopy and magnetization measurements, on SiO2 and Al2O3 substrates implanted with 4 at. % Fe, show ferromagnetic behaviour of α-Fe clusters in amorphous SiO2, but α-Fe2O3 clusters displaying superparamagnetic relaxation in crystalline Al2O3.
CRIS-Team Scopus Importer:2023-04-20
Keywords: ion-implantation; magnetic properties; nanostructure